The Influence of State Identity on Student Aggressivity - Siti Fauziah; Ayu Diah Nurjunima; Khodijah Auliya Tsabitta; Puan Harum Majid; Muhammad Almuzaffah (CV. Doki Course and Training, 2024)
Aggressiveness is behavior that hurts, injures, harms and is detrimental both physically and psychologically. State identity is organizing, encouraging, believing in oneself to make self-decisions. This research is limited, the purpose of this study is to determine the effect of state identity on aggressiveness in semester 4 students at Palembang city, South Sumatra, Indonesia. The total number of research respondents was 45 people. Data collection was carried out through a questionnaire with a quantitative research type. This research was developed with the development of Taufik's (2011) scale concerning the effect of identity status on aggressiveness. The results of the research analysis showed that the significance hypothesis test value was 0.43, the normality test was 0.48 and the linearity test was 0.14. Referring to the deviation from sign value of 0.05, it can be concluded that there is a significant relationship between state identity and the aggressiveness of 4th semester students.